PENAPISAN FITOKIMA DAN BILANGAN PEROKSIDA (POV) TIGA JENIS TUMBUHAN FAMILI MORACEACE (Artocarpus sp., A.elasticus, dan Ficus sp.) DARI TAMAN NASIONAL BOGANI NANI WARTABONE (SULUT) - Harapini, Mindarti; Praptiwi, Praptiwi (Research Center for Biology-Indonesian Institute of Sciences, 2003)
The Â aim of study were to determine the chemical compounds and peroxide values (POV) of methanol extract of three plants species belongs to Moraceae family (Artocarpus (Artocarpus sp., A.elasticus, dan Ficus sp.). Their chemical compounds were identified by Cuiley method, while peroxide value was done by iodometri titration. Methanol extract percentage ofÂ Artocarpus sp., A.elasticus, dan Ficus sp. were 20.80%, 3.10% and 4.10% respectively. All of the extract tested contained essential oil, sterol and triterpenoid, aglicon flavonoid, tannin, flavonoid glicoside and saponin. POV ofÂ Artocarpus sp., A.elasticus, dan Ficus sp. were 325.24, 306.25 and 1580.07 respectively and POV of q tocopherol was 363.96. So, it can be concluded taht all of three methanol extract act as reductor, because their POV less that POV of q tocopherol and might be act antioxidant. These correalted with their chemical compounds such as flavonoid, tannin and peroxide sugar.